2019
DOI: 10.1109/tac.2018.2838055
|View full text |Cite
|
Sign up to set email alerts
|

Invariance-Like Results for Nonautonomous Switched Systems

Abstract: This paper generalizes the LaSalle-Yoshizawa Theorem to switched nonsmooth systems. Filippov and Krasovskii regularizations of a switched system are shown to be contained within the convex hull of the Filippov and Krasovskii regularizations of the subsystems, respectively. A candidate common Lyapunov function that has a negative semidefinite derivative along the trajectories of the subsystems is shown to be sufficient to establish LaSalle-Yoshizawa results for the switched system. Results for regular and non-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Collecting ( 31), ( 32) and ( 36) we can conclude (29), and prove item B). We complete the proof by proving (34).…”
Section: Feedback Interconnection and Small Gain Theoremmentioning
confidence: 66%
See 1 more Smart Citation
“…Collecting ( 31), ( 32) and ( 36) we can conclude (29), and prove item B). We complete the proof by proving (34).…”
Section: Feedback Interconnection and Small Gain Theoremmentioning
confidence: 66%
“…For a large class of locally Lipschitz functions called non-pathological functions (as phrased in [49]), the notion of Lie derivative leads to less conservative stability conditions, see [6] and our recent papers [14] and [15]. As another example, the Lie derivative concept has been recently used in [28] to identify and remove infeasible directions of a differential inclusion of the form (2), and for stability analysis using an invariance principle for state-dependent switched systems [29], based on the ideas already introduced in [40].…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that a common candidate Lyapunov function with a negative semidefinite generalized time derivative along the trajectories of the subsystems suffices to establish invariance-like results [20,21]. Moreover, we use the contraction theory on Finsler manifold to analyze the convergent behavior between any pair of trajectories or solutions, which unfolds the incremental stability analysis to a more expansive and essential extend.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple Lyapunov functions for analyzing Lyapunov stability and iterated function systems as a tool for Lagrange stability is proposed in [15]. Invariancelike results for nonautonomous nonlinear switched systems are developed in [16]. Switched systems analysis of output feedback systems and observers have also been studied in the literature.…”
Section: Introductionmentioning
confidence: 99%